Redox-sensitive polymeric micelles with aggregation-induced emission for bioimaging and delivery of anticancer drugs - Sun, Changzhen (J Nanobiotechnology, 2021)
BACKGROUND: Nano-drug delivery systems show considerable promise for effective cancer therapy. Polymeric micelles have attracted extensive attention as practical nanocarriers for target drug delivery and controlled drug delivery system, however, the distribution of micelles and the release of the drug are difficult to trace in cancer cells. Therefore, the construction of a redox-sensitive multifunctional drug delivery system for intelligent release of anticancer drugs and simultaneous diagnostic imaging and therapy remains an attractive research subject. RESULTS: To construct a smart drug delivery system for simultaneous imaging and cancer chemotherapy, mPEG-ss-Tripp was prepared and self-assembled into redox-sensitive polymeric micelles with a diameter of 105 nm that were easily detected within cells using confocal laser scanning microscopy based on aggregation-induced emission. Doxorubicin-loaded micelles rapidly released the drug intracellularly when GSH reduced the disulfide bond. The drug-loaded micelles inhibited tumor xenografts in mice, while this efficacy was lower without the GSH-responsive disulfide bridge. These results establish an innovative multi-functional polymeric micelle for intracellular imaging and redox-triggered drug deliver to cancer cells. CONCLUSIONS: A novel redox-sensitive drug delivery system with AIE property was constructed for simultaneous cellular imaging and intelligent drug delivery and release. This smart drug delivery system opens up new possibilities for multifunctional drug delivery systems. [Image: see text]